A delay-based dynamic scheduling algorithm for bag-of-task workflows with stochastic task execution times in clouds - Cai, Zhicheng; Li, Xiaoping; Ruiz, Rubén; Li, Qianmu (Future generation computer systems, 2017)
Bag-of-Tasks (BoT) workflows are widespread in many big data analysis fields. However, there are very few cloud resource provisioning and scheduling algorithms tailored for BoT workflows. Furthermore, existing algorithms fail to consider the stochastic task execution times of BoT workflows which leads to deadline violations and increased resource renting costs. In this paper, we propose a dynamic cloud resource provisioning and scheduling algorithm which aims to fulfill the workflow deadline by using the sum of task execution time expectation and standard deviation to estimate real task execution times. A bag-based delay scheduling strategy and a single-type based virtual machine interval renting method are presented to decrease the resource renting cost. The proposed algorithm is evaluated using a cloud simulator ElasticSim which is extended from CloudSim. The results show that the dynamic algorithm decreases the resource renting cost while guaranteeing the workflow deadline compared to the existing algorithms. •Minimizing the cloud resource renting cost of bag-of-tasks workflows.•A bag-based delay triggering strategy is proposed to fully use the bag structure.•Using expectation-and-variance of execution times to estimate practical times.•A single-type based greedy method is developed for each ready BoT.